P Pelatihan Pijat Oksitosin pada Keluarga Ibu Hamil TM III dalam Peningkatan Dukungan Pemberian ASI Ekslusif di Klinik Pedungan Medika Denpasar - Pande Putu Indah Purnamayanthi; Ni Made Risna Sumawati; Putu Ayu Dina Saraswati (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
The purpose of this community service is to provide training to families of pregnant women in their third trimester, namely husbands, on how to do oxytocin massage independently. The method used is to collect respondents by holding a class for pregnant women in their third trimester at the Pedungan Medika Denpasar Clinic. The first implementation carried out was to provide counseling and then conduct demonstrations and training for pregnant women in their third trimester. Participants in this activity were pregnant women in their third trimester and their families at the Pedungan Medika Denpasar Clinic. It is hoped that after conducting the training, families, especially husbands, can do oxytocin massage on pregnant women in their third trimester at home so that mothers will be confident in breastfeeding their babies later.